Ultra-processed foods consumption associated with food addiction in Chilean young adults - Díaz-Torrente, Ximena; Valenzuela, Carina; Valenzuela, Michelle; Gearhardt, Ashley N. (Frontiers in Nutrition, 2026)
BackgroundUltra-processed foods (UPF), most of which have hyper-palatable properties, have been implicated in overconsumption and adverse health outcomes, yet their association with food addiction (FA) remains underexplored in young adults.AimTo assess the association between marker foods for UPF consumption and FA in Chilean university students, comparing UPF consumption among individuals with and without FA.MethodsIn a cross-sectional study, 287 young adults (median age: 21 years) completed the NOVA Screener -which captures the presence and number of UPF items consumed during the previous day- and the Chilean version of the Yale Food Addiction Scale 2.0 (YFAS 2.0-Chile). Anthropometric measurements and body composition were obtained for 271 participants. Logistic regression models were adjusted for gender, physical activity, and Body Mass Index (BMI).ResultsThe prevalence of FA was 17.4%, predominantly severe cases. Participants with FA had significantly higher median NOVA scores for beverages, snacks, and total UPF consumption. FA was positively associated with greater consumption of UPF beverages (OR 1.48, p = 0.014), snacks (OR 1.26, p = 0.044), and NOVA score (OR 1.12, p = 0.042). Individuals with FA also exhibited higher BMI and body fat percentage.ConclusionThese findings highlight a significant association between UPF consumption and FA in young adults, suggesting that UPF consumption may potentially contribute to addictive eating behaviors and associated metabolic risks. Public health strategies targeting UPF consumption may be essential in preventing FA and related health conditions.